Cardiac dysfunction in patients with brain hemorrhage - الكردي , عدي; عبدالله شيخ ابراهيم; عيسى لايقة (Latakia University Journal -Medical Sciences Series, 2023)
Background: the anatomical and physiological link between the nervous system and the cardiovascular system, assumes the influence of the two systems and the interference with normal and pathological functions, as the relationship between the two systems is complex and integrated, and some pathological conditions can interfere with the brain-heart axis leading to disturbance. Aim & Objective: study the effect of brain hemorrhage on systolic ,diastolic and electrophysiological cardiac function, and to shed light on the pathophysiological mechanisms of the interaction between the brain and the heart. Material & Methods: A Cohort Prospective study of 53 patients with intracerebral and subarachnoid hemorrhage. Patients were monitored and evaluated clinically on admission and underwent ECG, transthoracic echocardiography and laboratory evaluation of troponin I. Results: The cardiac changes in patients with cerebral hemorrhage varied according to the site of the hemorrhage and depend on the affected cerebral hemisphere (lateralization). Right insular cortex injury was associated with increased parasympathetic effects, left injury was associated with increased sympathetic effects. Electrocardiographic abnormality was in 39.6% of patients, the arrhythmia was 30.4%, the most common arrhythmia was atrial fibrillation 13.2% Troponin elevated in 20.8% of patients, 15.1% of them were associated with a disorder of systolic function and 52.8% with a disorder of diastolic function. Conclusion: These results related to the disturbance of each of the systolic, diastolic and electrophysiological functions of the heart showed the effect of brain hemorrhage on the brain-heart axis.